2009
DOI: 10.4315/0362-028x-72.7.1450
|View full text |Cite
|
Sign up to set email alerts
|

Listeria monocytogenes in the Irish Dairy Farm Environment

Abstract: Listeria monocytogenes is a potentially lethal foodborne pathogen commonly found in the environment. European Union hygiene legislation places responsibility for safety on primary production facilities, including farms, as part of a policy to introduce traceability throughout the food chain. This study aimed to determine the occurrence of L. monocytogenes in the Irish dairy farm environment and in particular the milking facility. Two hundred ninety-eight environmental samples were collected from 16 farms in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
71
6
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 102 publications
(81 citation statements)
references
References 31 publications
1
71
6
3
Order By: Relevance
“…Eight of the 43 isolates were from pregnant women, four were from neonates and the remaining 31 isolates were from non-pregnancy-associated adult cases, representing 62, 67 and 56 % of total Irish cases, respectively, over the period of 2004-2009. Species-level identification and serotyping. Presumptive-positive L. monocytogenes isolates were confirmed using biochemical testing as described in the international standard isolation protocols used (McClain & Lee, 1988; United States Department of Agriculture, 2008), or by real-time PCR as described by Fox et al (2009). Serotyping was performed using a combination of commercially available antisera (Denka Seiken), multiplex serotyping PCR (Doumith et al, 2004) and/or ELISA (Palumbo et al, 2003).…”
Section: Methodsmentioning
confidence: 99%
“…Eight of the 43 isolates were from pregnant women, four were from neonates and the remaining 31 isolates were from non-pregnancy-associated adult cases, representing 62, 67 and 56 % of total Irish cases, respectively, over the period of 2004-2009. Species-level identification and serotyping. Presumptive-positive L. monocytogenes isolates were confirmed using biochemical testing as described in the international standard isolation protocols used (McClain & Lee, 1988; United States Department of Agriculture, 2008), or by real-time PCR as described by Fox et al (2009). Serotyping was performed using a combination of commercially available antisera (Denka Seiken), multiplex serotyping PCR (Doumith et al, 2004) and/or ELISA (Palumbo et al, 2003).…”
Section: Methodsmentioning
confidence: 99%
“…In dairy farms, the principal places where Listeria can be found are soil, water and forage (Sauders & Wiedmann, 2007). Fox et al (2009) determined the occurrence of L. monocytogenes in the dairy farm environment, and particularly in milking facilities, showing a relatively high prevalence (19%) of L. monocytogenes in 298 environmental samples from 16 farms in Ireland. They also detected a correlation between the level of hygiene standards on the farm and the occurrence of the pathogen in the environment (water, soil, silage, cow faeces, milk, etc.…”
Section: Listeria Monocytogenes In the Dairy Farm Environmentmentioning
confidence: 99%
“…Some specific subtypes of L. monocytogenes can also persist for extended periods in many different food processing environments , including dairy food processing plants (Vazquez-Villanueva et al, 2010;Latorre et al, 2011). In the dairy plant, Listeria can persist in a variety of sites, although it is most frequently found in moist environments or areas with condensed or standing water or milk, including drains, floors, coolers, conveyors and case washing areas (Arimi et al, 1997;Ho et al, 2007b;Fox et al, 2009).…”
Section: Processing Environmentmentioning
confidence: 99%
“…L. monocytogenes has been isolated from a variety of environmental sources, e.g., water, soil, silage, vegetation, and food processing plants (3,17,18,23,29,42). A number of studies have reported a high prevalence of L. monocytogenes in dairy farm environments (5,19,21,33,55). In addition, a previous study has found a considerably higher prevalence of L. monocytogenes in dairy farm environments than in urban and natural environments (45).…”
mentioning
confidence: 99%